Efektivitas Dimensi Individu, Kelembagaan, dan Lingkungan dalam Pemberdayaan Masyarakat Petambak melalui Implementasi Inovasi Teknologi - Mira Mira (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2014)
The purpose of this study is to analys the factors that influence effectiveness of community empowerment program. The study was conducted in 2012-2013, in three villages of Brebes Regency (Randusanga, Grinting, and Kaliwlingi). The study uses principal component analysis. Screen plot analysis indicates tenth elements used are the most decisive factor in the effectiveness of community empowerment. It is indicated on the graph that decreases sharply on the element 1 to element 2, and very sharply decreases on element 2 to element 3, and slightly sloping from the element 3 to element 10. The ten elements when sorted by priority are the ability of individual farmers, economic conditions, ponds physical condition, Klinik Mina Bisnis institutional leadership, technology used in farming, the role of farmers, relationships with target groups, systems and institutional structures, motivation, social and cultural. Communalities value analysis indicates all factors to assess the effectiveness of community empowerment has a strong relationship with the model is formed, because the value of all the communalities elements is above 50persen. The greatest communalities value is the ability of individual farmers (0.868), indicating 86.8 persen variance of the ability of individual variables can be explained by factors formed. Individual ability of marine and coastal community in Brebes Regency in accepting innovation from the Ministry of Marine and Fisheries is very high, this indicates target group easily adopt any technological innovation introduced by The Ministry of Marine and Fisheries. The smallest communalities value is sociocultural (0.622), it means social and cultural element is less supportive for community empowerment. Farmers in the study area are individualistic, every problem is solved individually.